The impact of HAART on sexuality and medicine taking behaviours among people living with HIV/AIDS in Grahamstown - Chizanga, Tongai Aldridge (Rhodes University, Faculty of Pharmacy, Pharmacy, 2010)
Introduction: Adherence to Highly Active Antiretroviral Therapy (HAART) is critical for optimal therapeutic outcomes. A possible factor in adherence is the impact of HAART on sexual functioning. Methods: A mixed methods approach was used. A cohort of 14 people living with HIV/AIDS (PLWHA) in Grahamstown was identified. Two semi-structured interviews and two structured questionnaires were administered. In-depth interviews were conducted with two HIV counsellors in so as to obtain a different perspective on the topics. The theoretical framework used three health behaviour models: the Health Belief Model, Leventhal's Common-Sense Model of self regulation and the Transtheoretical model. Results: The participants were between 27 and 49 years old and had been on HAART for between 9 months and 10 years. Six participants were support staff members from Rhodes University and eight from the Raphael Centre "“ a local NGO which assists PLWHA.In most of the participants HAART was associated with increased libido and improved sexual functioning (sexual activity and sexual enjoyment). The use of alcohol increased risky sexual behaviour. Issues of adherence were seemingly not directly affected by the effects of HAART on sexuality. PLWHA, especially women, face challenges related to their sexuality, some of which are not directly related to their illness and treatment. The fear of transmitting drug resistant HIV or getting re-infected, stigma, disclosure issues,difficulties negotiating for safe sex among women, HAART-related lipodystrophic changes that affect one's sense of self and unmet reproductive needs are some of the problems that were reported. The men's dislike for condoms was overt and blatant. Discussion: Being diagnosed with HIV and reaching a point where treatment is requiredare life-changing events. Making decisions about one's life (including adherence to HAART, alcohol use and knowingly partaking in risky sexual encounters) become all the more significant in the context of AIDS. Intentional non-adherence is informed by the individual's assessment of the costs and benefits of taking treatment. Cultural influences,gendered power relations and misconceptions strongly influence sexual behaviours. Conclusion: The general lack of attention among health care providers concerning issues related to PLWHA's sexuality and reproductive issues needs to be addressed. Insights fromthe theoretical models should be integrated with empirical findings in designing adherence interventions.
Keywords: AIDS (Disease) -- Treatment -- South Africa -- Grahamstown; HIV infections -- Treatment -- South Africa -- Grahamstown; Antiretroviral agents -- South Africa -- Grahamstown; Patient compliance -- South Africa -- Grahamstown; AIDS (Disease) -- Social aspects -- South Africa -- Grahamstown; HIV infections -- Social aspects -- South Africa -- Grahamstown; AIDS (Disease) -- Patients -- South Africa -- Grahamstown -- Sexual behavior; HIV-positive persons -- South Africa -- Grahamstown -- Sexual behavior; Patient education -- South Africa -- Grahamstown